Response to Bollig and Zelco - Matthew Hooper; Marius Rehn (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract In this reply we discuss the comments raised by Bollig and Zelco on our Editorial on Emergency Last Aid (ELA). We focus on that ELA is a clinician-focused educational initiative specifically tailored for those working in high-acuity, high-consequence settings such as pre-hospital, emergency, and critical care environments. The course is designed specifically for clinicians operating in environments where leadership, decision-making, and compassionate communication often occur under intense pressure, frequently with limited time and support.